Tata Kelola BUMDes Gajah Mandiri Desa Bakal Gajah Kecamatan Silima Pungga-Pungga Kabupaten Dairidalam Rangka Peningkatan Pendapatan Asli Desa - Tarigan, Ridawaty; Harahap , R. Hamdani; Kusmanto, Heri (PERSPEKTIF, 2024)
BUMDes (Village-Owned Enterprises) are vital in increasing Village Original Income (PAD) as per Law No. 6 of 2014. Therefore, the development of BUMDes is crucial and requires proper governance. This study aims to analyze the governance of BUMDes Gajah Mandiri in Bakal Gajah Village, Silima Pungga-Pungga Subdistrict, Dairi Regency, and identify the driving and inhibiting factors in its management. The governance of BUMDes is reviewed based on the concept of Good Corporate Governance, which includes the principles of disclosure, transparency, and responsibility. This study uses a qualitative method with a descriptive approach, involving in-depth interviews, observation, and documentation techniques. The analysis found that while the principles of fairness and accountability have been implemented, deficiencies still affect the performance of BUMDes employees and management. The driving factors for the governance of BUMDes Gajah Mandiri in increasing PAD include the entrepreneurial spirit of the management, support from the village government, sufficient capital, trust and participation from the community, and training from the Ministry of Villages. The inhibiting factors are the lack of support from the district government and PMD, limited capital, natural disasters, and lack of professionalism in human resources.